Sistem Pendukung Keputusan Penerimaan Siswa Baru di SMK Fajar Bogor menggunakan Metode SAW - Muhammad Faiz Burhanuddin; Abdurahman Abdurahman; Ek Ajeng Rahmi Pinahayu (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The problem of decision making for admitting new students at SMK Fajar Bogor is that they still use Microsoft Excel so they experience several obstacles and a lack of systematicity in decision making regarding new students at SMK Fajar Bogor. This research aims to design an application to make the processing of prospective new students' grades easier and to design a more systematic decision-making application regarding the admission of new students to SMK Fajar Bogor. This research identifies the criteria for diploma grades, test scores, psychological test scores and zoning. The Simple Additive Weighting (SAW) method was used to design, develop and test a decision support system at the SMK Fajar Bogor school. This system is designed using the PHP programming language and MYSQL database. The results of the research are that the process of processing the grades of prospective new students becomes easier, decision making regarding the acceptance of new students at SMK Fajar Bogor becomes more systematic.